Hydrogel adhesive formed via multiple chemical interactions: from persistent wet adhesion to rapid hemostasis. (15th February 2022) - Liang, Min; Wei, Dandan; Yao, Zhangyu; Ren, Pengfei; Dai, Jidong; Xu, Li; Zhang, Tianzhu; Zhang, Qianli
Abstract : A physicochemically double cross-linked hydrogel was developed, which presents rapid hemostasis performance as well as persistent wet adhesion. Abstract : To date, the robust and durable adhesion capability of hydrogel adhesives in wet environments remains a huge challenge. Herein, a physicochemically double-network crosslinked hydrogel matrix was prepared by mixing acrylic acid (AAc), chitosan (CS) and tannic acid (TA) as the main components and the subsequent in situ polymerization of AAc. The abundant reactive sites on the surface of the hydrogel matrix facilitate rapid, strong and repeatable adhesion to different surfaces of engineering solids and biological tissues in an aquatic environment. The formation of amide covalent bonds resulting from the addition of the bridging agent further expands the long-term application of the hydrogel in tissue repair, and the constructed hydrogel-tissue adhesive interface still has robust adhesion energy after soaking in a physiological environment for up to one month. Moreover, the hydrogel showed fantastic hemostatic performance due to its characteristics of platelet adhesion and high burst pressure. Overall, the persistent adhesion and excellent cytocompatibility of the hydrogel adhesive make it potentially applicable in medical adhesives.